(untitled) (Health Renaissance, 2015)
Mesenteric cystic lymphangiomas (MCLs) are uncommon benign cystic tumours of unknown aetiology, most often seen in paediatric patients. The clinical presentation ranges from an incidentally discovered abdominal cyst to symptoms of acute abdomen. A10-year-old male presented with generalized abdominal pain, nausea and vomiting & constipation of several hours duration. Emergency laparotomy revealed multiple cystic masses along both the sides of sigmoid colon and mesocolon, which were inflammed mimicking diverticulosis. Sigmoidectomy with colorectal anastomosis was performed. The postoperative course was uncomplicated. MCLs should be included in the differential diagnosis of cystic intra-abdominal lesions. Even when asymptomatic and discovered incidentally, they must be treated surgically because of the potential to grow, invade vital structures and develop life-threatening complications. Health Renaissance 2014;12(2): pp: 130-132